Hubungan Antara Penguasaan Silang Budaya dan Kemampuan Komunikatif - Muhammad Farkhan (Buletin Al-Turas, 2007)
This Correlational study aims at knowing empirically the significant relation between the third yearsstudents cross-cultural understandind and communcative competence at state islamic senior high school at South Jakarta.Its data that are obtained through two kinds of test are analyzed using both regression and correlation technique.The data analysis shows that the correlation coefficient of this research is 0.77; while in the significance levelof 0.005 with 60 students as a sample of the research the Pearson's table indicates the correlation coefficient is bigger than the value of the Pearson's table, the null hypotesis can be rejected and the alternative one is accepted.Therefore, it can be understood that there is significant relation between the third year student's cross-culturalunderstanding and communicative competence at State Islamic Senior High School at South Jakarta.